Analysis of Community Interest in Sports at Rawamangun Velodrome Area - Setyo Dwi Argha Pramudya; Qorry Armen Gemael; R. Retna Kinanti Dewi; Habibi Hadi Wijaya (UNIVERSITAS NEGERI MAKASSAR, 2023)
Sport is physical activity carried out systematically, regularly, planned and sustainably to maintain and develop physical, spiritual and social health. Jakarta International Velodrome Rawamangun has facilities for the public to carry out sports activities. Sports facilities are one of the reasons for increasing people's interest in doing sports activities. The aim of this research is to find out how interested the public is in sports at the Jakarta International Velodrome, East Jakarta City. This research method uses a quantitative approach using a survey method. The population is people who carry out sports activities at the Jakarta International Velodrome Rawamangun. The sample was determined using the Slovin formula with a population of 180/day sourced from data from the Rawamangun Velodrome management. So the total sample is 125 people. The sampling technique uses accidental sampling. This research variable is interest. This research interest describes feelings of interest, comfort, emotions, experiences, facilities, activities, geographical conditions and friends. The research instrument used a questionnaire of 20 questions. Data analysis uses descriptive methods. The research results explained that 98.4% of respondents had a high interest in carrying out sports activities at the Jakarta International Velodrome Rawamangun.